2009
DOI: 10.5993/ajhb.33.5.14
|View full text |Cite
|
Sign up to set email alerts
|

Protective Behaviors and High-Risk Drinking Among Entering College Freshmen

Abstract: Objectives-To explore the use of protective behaviors to reduce risks associated with alcohol consumption among adolescents during the summer preceding college enrollment.Methods-Survey data were collected in fall 2006 and 2007 that assessed demographic characteristics, drinking behaviors, and use of protective behaviors in the 3 months preceding the survey.Results-Female participants reported using 4 out of 10 protective behaviors more often than did males, and using protective behaviors was significantly rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…We found that after controlling for alcohol use, the magnitude of the association between PBS and alcohol-related problems was stronger for women than men, although the effect size was quite small (difference in R 2 = 0.002 or 0.2% variance), which is not unusual for moderation effects. Previous studies found similar results among freshmen (Sutfin et al, 2009) and undergraduates (Delva et al, 2004; Sutfin et al, 2009) sampled from a single university. Our study extends the current literature by increasing the generalizability of these findings because undergraduate students from different academic years were sampled from several colleges across the United States.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We found that after controlling for alcohol use, the magnitude of the association between PBS and alcohol-related problems was stronger for women than men, although the effect size was quite small (difference in R 2 = 0.002 or 0.2% variance), which is not unusual for moderation effects. Previous studies found similar results among freshmen (Sutfin et al, 2009) and undergraduates (Delva et al, 2004; Sutfin et al, 2009) sampled from a single university. Our study extends the current literature by increasing the generalizability of these findings because undergraduate students from different academic years were sampled from several colleges across the United States.…”
Section: Discussionsupporting
confidence: 67%
“…Numerous studies have found that women, relative to men, were more likely to utilize PBS, although gender differences in specific types of PBS are unclear, in part because different PBS measures have been utilized in the literature (e.g., Delva et al, 2004; Sutfin et al, 2009; Walters, Roudsari, Vader, & Harris, 2007). To our knowledge, previous studies have not examined whether racial differences in the utilization of specific types of PBS at the item level differ for men and women.…”
Section: Race and Gender Differences In Pbs Usementioning
confidence: 99%
“…One possible explanation for fewer consequences is that females use protective behavioral strategies, such as using a designated driver, eating during or before drinking, and switching between alcohol and non-alcoholic beverages, more often than males do. 44 This could also be due to the increased drinking of women, in general. In secondary analysis of over 43,000 participants in the US National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), Keyes and colleagues 45 found that gender differences in alcohol disorders were decreasing simply because women were drinking more.…”
Section: Discussionmentioning
confidence: 99%
“…This use of the more narrow definition appears to be most consistent with current use of the term PBS. In fact, only 13 of the 62 studies (~21%) used the broader definition, and this includes studies that had only one or two alcohol avoidance strategies (e.g., NCHA, Sutfin et al, 2009). Although this fact certainly does not reflect a pure consensus, it does suggest that most PBS researchers find the more narrow definition more useful for their research aims.…”
Section: Measurement Of Pbsmentioning
confidence: 99%
“…Specifically, women have been found to use more PBS when examined as a single factor (Benton et al, 2004; Benton, Benton, & Downey, 2006; Benton, Downey, Glider, & Benton, 2008; Borden et al, 2011; D’Lima, Pearson, & Kelley, 2012; Ehret, Ghaidarov, & LaBrie, 2013; Frank, Thake, & Davis, 2012; Palmer, McMahon, Rounsaville, & Ball, 2010; ), multiple factors (Nguyen, Walters, Syatt, & DeJong, 2011) including all PSQ subscales (DeMartini et al, 2013), all PBSS subscales (LaBrie, Lac, Kenney, & Mirza, 2011; Lewis, Rees, & Lee, 2009; Lewis, Rees, Logan, Kaysen, & Kilmer, 2010), and all SQ subscales (Pearson & Henson, 2013). Of all the studies reviewed, only four studies report any non-significant gender differences in PBS use, and each of these studies found some significant gender differences (Pearson, Kite, and Henson, 2012a; Sutfin et al, 2009; Walters et al, 2007; Werch, 1990). Overall, there is overwhelming evidence that women use more PBS than men.…”
Section: Antecedents/predictors Of Pbs Usementioning
confidence: 99%